Intangible impacts assessment of r & d: development of methodology used in public research centres (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2010)
The generation of intangible assets is one of the most significant research and development (R & D). Undeniably, the role that intangibles such as input and output in the process of technology development. Find ways to demonstrate the intangible impacts of R & D generated from the viewpoint of knowledge creation, and political-institutional training is very important to public organizations of R & D for two reasons. First to address future R & D efforts and to demonstrate the effects that these impacts have on improving the living conditions of people working in agriculture and society in a general way. This work demonstrates the construction process of impact assessment methodology used intangibles Embrapa (Brazilian Agricultural Research Company), a public research organization in Brazil.
Keywords: assessment of impacts of R & D,; Intangibles; Knowledge